The Structure of Neisseria meningitidis Lipid A Determines Outcome in Experimental Meningococcal Disease - Fransen, Floris (American Society for Microbiology (ASM), 2010)
Lipopolysaccharide (LPS), a major component of the meningococcal outer membrane, is sensed by the host through activation of Toll-like receptor 4 (TLR4). Recently, we demonstrated that a surprisingly large fraction of Neisseria meningitidis disease isolates are lipid A mutants, due to inactivating mutations in the lpxL1 gene. The lpxL1 mutants activate human TLR4 much less efficiently than wild-type bacteria, which may be advantageous by allowing them to escape from the innate immune system. Here we investigated the influence of lipid A structure on virulence in a mouse model of meningococcal sepsis. One limitation, however, is that murine TLR4 recognizes lpxL1 mutant bacteria much better than human TLR4. We show that an lpxL2 mutant, another lipid A mutant lacking an acyl chain at a different position, activates murine TLR4 less efficiently than the lpxL1 mutant. Therefore, the lpxL2 mutant in mice might be a better model for infections with lpxL1 mutants in humans. Interestingly, we found that the lpxL2 mutant is more virulent in mice than the wild-type strain, whereas the lpxL1 mutant is actually much less virulent than the wild-type strain. These results demonstrate the crucial role of N. meningitidis lipid A structure in virulence.